2022
DOI: 10.1190/int-2021-0197.1
|View full text |Cite
|
Sign up to set email alerts
|

Pore structure analysis of tight reservoirs in He-8 Member of Upper Paleozoic in the southwestern Ordos Basin, China

Abstract: Quantitative characterization of the pore structure in tight reservoir can provide basic parameters for the evaluation of the reservoir quality. By using the cast thin-section petrography, scanning electron microscopy, mercury injection capillary pressure, and constant-rate mercury injection, we have evaluated the distribution characteristics of pore throat and its contribution to permeability. In addition, we have established the relationship between different pore-throat structure parameters and reservoir ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The present-day structure exhibits a large monocline feature, with higher elevations in the east and south and lower elevations in the west and north. The Upper Paleozoic succession comprises the Carboniferous Benxi Formation, Permian Taiyuan Formation, Shanxi Formation, Shihezi Formation, and Shiqianfeng Formation [2]. These formations represent a transitional sequence of continental to marine clastic rock deposits.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The present-day structure exhibits a large monocline feature, with higher elevations in the east and south and lower elevations in the west and north. The Upper Paleozoic succession comprises the Carboniferous Benxi Formation, Permian Taiyuan Formation, Shanxi Formation, Shihezi Formation, and Shiqianfeng Formation [2]. These formations represent a transitional sequence of continental to marine clastic rock deposits.…”
Section: Geological Settingmentioning
confidence: 99%
“…Oil and gas exploration practices have demonstrated that tight sandstone gas reservoirs are crucial targets for natural gas exploration [1][2][3]. The Shan-1 Member of the Permian Shanxi Formation in the Southwest (SW) Ordos Basin represents a tight reservoir.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation